2008
DOI: 10.1088/0967-3334/29/10/r01
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance electrical impedance tomography (MREIT) for high-resolution conductivity imaging

Abstract: Cross-sectional imaging of an electrical conductivity distribution inside the human body has been an active research goal in impedance imaging. By injecting current into an electrically conducting object through surface electrodes, we induce current density and voltage distributions. Based on the fact that these are determined by the conductivity distribution as well as the geometry of the object and the adopted electrode configuration, electrical impedance tomography (EIT) reconstructs cross-sectional conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
213
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 195 publications
(215 citation statements)
references
References 75 publications
1
213
0
1
Order By: Relevance
“…In this feasibility study, current density mapping of living tissues was found to be possible using a recently developed MREIT method. 7,9,12 Since induced current density depends on the electrode position and current amplitude as well as the local conductivity distribution, 2,5,7 we obtained magnetic flux density (B z ) data from the MREIT scan to image the current density distribution during DBS. Instead of using Ampere's law directly, we recovered projected current density which is the best current density measured from one component of magnetic flux density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this feasibility study, current density mapping of living tissues was found to be possible using a recently developed MREIT method. 7,9,12 Since induced current density depends on the electrode position and current amplitude as well as the local conductivity distribution, 2,5,7 we obtained magnetic flux density (B z ) data from the MREIT scan to image the current density distribution during DBS. Instead of using Ampere's law directly, we recovered projected current density which is the best current density measured from one component of magnetic flux density.…”
Section: Discussionmentioning
confidence: 99%
“…A similar method, magnetic resonance electrical impedance tomography (MREIT) can image current density of living tissues using only one component of B without rotating the subject. [12][13][14] In addition, the conductivity distribution of living tissues can be obtained from two independent current injection data inside the imaging objects. 7,9,12 From numerical simulation and mimicked phantom experiments, 12,15,16 several studies have proposed that this method has a potential for visualizing current density distribution in living tissues.…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 99%
“…It is an EIT type conductivity reconstruction method, which uses internal current data (see [21,22,24]). The internal magnetic field B is obtained using MRI technology and the internal current density data J is obtained by Ampere's Law…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve the technical difficulties in EIT and to achieve high spatial resolution and high accuracy in conductivity imaging, magnetic resonance electrical impedance tomography ͑MREIT͒ was developed by combining EIT and magnetic resonance current density imaging ͑MRCDI͒ technique. 9,10 In MREIT, a MRI scanner is used to detect the induced magnetic field generated by injected current flowing in biological tissues. Till now, conductivity images with high spatial resolution have been obtained using the MREIT technique in both in vitro and in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Till now, conductivity images with high spatial resolution have been obtained using the MREIT technique in both in vitro and in vivo experiments. 9 Currently, MREIT is mainly limited by its requirement of high level current injection to obtain an acceptable signal-to-noise ͑SNR͒ level. Recently, some researchers have also proposed to extract electrical properties of human body at Larmor frequency using MRI B1 mapping technique.…”
Section: Introductionmentioning
confidence: 99%